METHODS OF SOIL PROCESSING, THE INFLUENCE OF SOWING NORMS AND MINERAL FERTILIZERS ON THE PROCESSES OF IRRIGATION EROSION OF THE SOIL - I.N.Xoshimov; B.B.Gulomov (Galaxy International Interdisciplinary Research Journal, 2021)
This article describes the effects of elements of agronomic measures (tillage methods, seed sowing and mineral fertilizer norms) applied to irrigation water and erosion processes used in the care of winter wheat on irrigated eroded lands.